2003
DOI: 10.1046/j.1365-2141.2003.04673.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and kinetic characterization of granulocyte colony‐stimulating factor‐primed CD34 human stem cells

Abstract: Summary.We assessed the functional properties and the kinetic status in vitro, and the engraftment potential in vivo of human haematopoietic stem cells according to the expression of CD34 antigen. Lin ) CD34 ) and Lin ) CD34 + cells were isolated from granulocyte colony-stimulating factor-primed peripheral blood (PB) cells of healthy donors. The CD34 ) cell fraction did not contain either clonogenic cells in semisolid culture or long-term culture initiating cells (LTC-IC). However, stroma-dependent liquid cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 46 publications
5
36
0
Order By: Relevance
“…5,15,16 Previous studies suggested that circulating progenitor cells differ from their BM counterparts with respect to cell-cycle characteristics and proliferative response to cytokines, [17][18][19][20] which is also reflected in our finding of differential ERK phosphorylation and may reflect effects mediated by the microenvironment.…”
Section: Discussionsupporting
confidence: 69%
“…5,15,16 Previous studies suggested that circulating progenitor cells differ from their BM counterparts with respect to cell-cycle characteristics and proliferative response to cytokines, [17][18][19][20] which is also reflected in our finding of differential ERK phosphorylation and may reflect effects mediated by the microenvironment.…”
Section: Discussionsupporting
confidence: 69%
“…[4][5][6]15 However, the CD34 neg fraction suffers from a profound impairment in migration after IV transplantation compared with the CD34 pos fraction. 5,7,8,11,13,[49][50][51][52] Our flow cytometric and western blot data revealed a more pronounced E-selL activity on the CD34 pos subset of the Lin neg CD38 neg fraction than on the CD34 neg subset, suggesting that the enhanced migratory ability of CD34 pos cells is due to its possession of a specific set of functional E-selLs, required for proper migration and homing of HSPCs. In agreement with these results, a previous study illustrated that BM and fetal liver-derived CD34 pos subsets rolled over immobilized E-selectin with higher efficiency than CD34 neg subsets.…”
Section: Discussionmentioning
confidence: 90%
“…The expression of human CD45 antigen in the BM and PB of mice that underwent transplantation was confirmed by reverse-transcription-polymerase chain reaction (RT-PCR) and Southern blotting as previously reported. 25 For comparative homing assessment in the BM and PB samples, CD34 ϩ CD45 ϩ cells were further evaluated for their relative content in PKH67-and PKH26-positive cells (ie, cells treated with UTP or mock medium, respectively).…”
Section: Adhesion Assaymentioning
confidence: 99%
“…Genes showing a detection called "A" (absent) in all samples were excluded. 25 The generated lists and, independently, the GCOS-generated absolute analysis data were uploaded onto GeneSpring software version 7.2 (Silicon Genetics, Redwood City, CA). To normalize data, each measurement was divided for the 50th percentile of all signals in that sample.…”
Section: Microarray Analysismentioning
confidence: 99%